Income groups and types of employment in Germany since 1995 - Peter Krause; Christian Franz; Marcel Fratzscher (DIW Economic Bulletin, 2017)
This report examines how income groups and forms of employment in Germany have changed in the past two decades. Since the mid-1990s, inequality in disposable household income in Germany has generally increased. This trend was in effect until 2005. While fewer people had disposable incomes in the median range, the proportion of the population at both tails of the income distribution increased. At the same time, there were many changes in the labor market. Employment rose, working hours became increasingly differentiated, and starting in 2005, the unemployment rate fell. While the employment increase was spread across almost all income groups, it was reflected differently in each group. The proportion of people with low wages in the income groups below the median rose steadily during the two decades studied. At the same time, in 2014-15 more people in high income groups had regular types of employment than they did in the second half of the 1990s. In the groups in the median range, regular types of employment were recently as frequent as they were 20 years ago and unemployment also declined here. Further, in these groups the proportion of those with jobs paying low wages is higher.
Keywords: D31; I31; I32; J62; 330; income inequality; labour market participation; precarious living; conditions; SOEP